2016
DOI: 10.1111/bju.13425
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and sequela of lymphocele formation after robot‐assisted extended pelvic lymph node dissection

Abstract: ObjectiveTo determine an accurate incidence of lymphocele formation and its sequela after robot-assisted radical prostatectomy (RARP) and extended lymph node dissection (eLND) in a contemporary prostate cancer cohort. Patients and MethodConsecutive patients who underwent RARP and eLND and had a minimum follow-up of 3 months were included. All surgeries were performed by one surgeon via a transperitoneal approach, with patients uniformly receiving low-molecular-weight heparin. Patients were followed with serial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
46
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 25 publications
(43 reference statements)
5
46
2
2
Order By: Relevance
“…Pelvic lymphocele is typically found incidentally during routine CT follow-up after surgery; however, it is sometimes symptomatic, requiring treatment [9][10][11]21]. In gynaecology and urology, several studies have shown that pelvic lymphocele is one of the most common complications after pelvic lymphadenectomy [12,13,22,23]. There have been many studies reporting complications associated with LPND following rectal cancer surgery [24][25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pelvic lymphocele is typically found incidentally during routine CT follow-up after surgery; however, it is sometimes symptomatic, requiring treatment [9][10][11]21]. In gynaecology and urology, several studies have shown that pelvic lymphocele is one of the most common complications after pelvic lymphadenectomy [12,13,22,23]. There have been many studies reporting complications associated with LPND following rectal cancer surgery [24][25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…In gynaecological studies, the incidence of all lymphoceles and symptomatic lymphoceles has been reported to be 18-38% and 3.4-24.6%, respectively [9,13,14,[33][34][35]. In urology, these rates have been reported to be 8.8-26% and 3.9-9%, respectively [15,16,23,36]. In our study, the incidence of all lymphoceles and symptomatic lymphoceles was 30.6% and 9.2%, respectively, indicating that it is not a rare complication after rectal cancer surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Keskin et al [5] reported a quite high incidence of lymphoceles within 1 month after RARP when performing US follow-up after RARP; most of the lymphoceles (76%) had disappeared by 3 months. However, a significant number (64%) of the lymphoceles that did persist over 3 months after RARP became symptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…Наш опыт показывает, что длительная лимфорея и лимфокисты являются одними из причин увеличения сроков гос-питализации. При этом, по данным недавней работы M. S. Keskin и соавт., симптоматическое лимфоцеле развивается только в 2,5 % случаев после минимально инвазивной РПЭ, а необходимость дренирования воз-никает только в 1,3 % всех вмешательств [31]. Наши результаты продемонстрировали отсутствие различий в частоте отсроченного дренирования таза по поводу лимфокист между группами пациентов, которым интра операционно страховой дренаж устанавливали или нет.…”
Section: Discussionunclassified